Predictive Factors For Choledocholithiasis In Patient Undergoing Cholecystectomy in Ibn Sina Specialized Hospital From 1/1/2019 - 1/1/2020 - Hamad, Mohammed Adel; Mussad, Abdelmajed Mohamed; Arabi, Nassir Alhaboob (Gezira Journal of Health Sciences, 2020)
Background: Choledocholithiasis constitutes the main aetiology of non-malignant biliary obstructions. The prevalence of CBD stones in patients with symptomatic gallstones varies but probably lies between 8 % and 20%. Failure to detect CBD stones leads to potentially life-threatening complications such as cholangitis, pancreatitis or obstructive jaundice. ERCP, MRCP and Intraoperative cholangiography have high sensitivity in detecting CBDS but its routine use is associated with increased complications, costs and operating room time. In this study we felt a need for useful predictive factors to predict patients having choledocholithiasis so that these modern interventions can be selectively utilized, and to determine the patients who need CBD exploration during cholecystectomy. Patient and Methods : Data was collected from consecutive patients diagnosed with cholelithiasis and choledocholithiasis by clinical presentations, ultrasonography and liver function tests at Ibn Sena Hospital, then CBD stone confirmed by  definitive testing for choledocholithiasis ( ERCP, MRCP or common bile duct [CBD] exploration). These clinical, biochemical and radiological findings were considered as predictive factors and analysed retrospectively. Results: A total of 72 patiens satisfied our inclusion criteria. Of those, 86% (n=62) had CBD stone, and 14% (n=10) did not have CBD stone. Several variables were analysed and showed that total bilirubin, ALP, AST, ALT, dilated CBD>6mm and visible CBD stone on ultrasonography were significantly associated with choledocholithiasis (p<0.05). Then four predictive factors (total bilirubin, ALP, dilated CBD > 6mm and visible CBDS on ultrasonography )  were used to build a simple scoring system. Conclusion: our results showed that abnormal liver function tests, multiple gallbladder stones, dilated CBD more than 6mm and visible CBD stone in ultrasonographic were statistically significant for detection of choledocholithiasis. Also we suggest a simple scoring system as a predictor for CBD stones.